IMPLEMENTASI METODE OUTDOOR LEARNING TERHADAP COMPLEX PROBLEM SOLVING SKILLS PADA MATA PELAJARAN IPA SISWA KELAS V SDN 56 PEKANBARU - Maisya, Riyanda; Hermita, Neni; Noviana, Eddy; Alpusari, Mahmud (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
The purpose of this study was conducted to determine differences in students' complex problem solving skills before and after the application of outdoor learning methods. This study uses a Pre-Experimental Design research method using one group pretest posttest design with a total of 19 students. The results of the study stated that in the pretest has an average value of 49.05 with the highest value of 76 and the lowest value of 11. After being given treatment using outdoor learning methods, the results of complex problem solving skills of students increased significantly namely having an average value of 60 with the highest value of 83 and the lowest value is 16. The average increase in the pretest and posttest is 0.21 with low interpretation. Therefore it can be concluded that there are differences in complex problem solving skills of students of class V SDN 56 Pekanbaru.